Genetic Diversity Analysis Reveals Genetic Differentiation and Strong Population Structure in Calotropis Plants - Muriira, Nkatha G. (Sci Rep, 2018)
The genus Calotropis (Asclepiadaceae) is comprised of two species, C. gigantea and C. procera, which both show significant economic potential for use of their seed fibers in the textile industry, and of their bioactive compounds as new medicinal resources. The available wild-sourced germplasm contains limited genetic information that restricts further germplasm exploration for the purposes of domestication. We here developed twenty novel EST-SSR markers and applied them to assess genetic diversity, population structure and differentiation within Calotropis. The polymorphic information index of these markers ranged from 0.102 to 0.800; indicating that they are highly informative. Moderate genetic diversity was revealed in both species, with no difference between species in the amount of genetic diversity. Population structure analysis suggested five main genetic groups (K = 5) and relatively high genetic differentiation (F(ST) = 0.528) between the two species. Mantel test analysis showed strong correlation between geographical and genetic distance in C. procera (r = 0.875, p = 0.020) while C. gigantea showed no such correlation (r = 0.390, p = 0.210). This study provides novel insights into the genetic diversity and population structure of Calotropis, which will promote further resource utilization and the development of genetic improvement strategies for Calotropis.